Scintillation, phonon and defect channel balance, the sources for fundamental yield increase - Gektin, A.; Vasil'ev, A. (Functional Materials, 2016)
The estimation of the fundamental limits of scintillation efficiency requires the analysis not only of electron channel of the energy transformation but also of the role of interplay between electron and phonon channels. The well-known factor beta which estimates the efficiency of electron-hole pair production is determined by the balance of these channels at the cascade and thermalization stages. The attention is paid to phonon production and relaxation at different stages of energy transformation in scintillators, starting from linear processes of emission of bulk phonons to multiphonon processes resulting in the production of local phonons and transient defect creation. The analysis shows that transient defects can play some positive role, being the centers of exciton stabilization. The spatial and temporal evolution of phonon subsystem and its interaction with electron subsystem in scintillators is analyzed. The role of phonons in the regions of high density of excitations (final region of tracks of primary and delta-electrons) is underlined. Possible experiments with simultaneous detection of these two channels are discussed.